2020
DOI: 10.1080/14763141.2020.1830163
|View full text |Cite
|
Sign up to set email alerts
|

The effect of course format on student learning in introductory biomechanics courses that utilise low-tech active learning exercises

Abstract: Low-tech active learning (AL) exercises in face-to-face (F2F) undergraduate biomechanics courses improve student learning vs. lecture alone. This study compared learning of biomechanics concepts with AL implemented in two course formats (hybrid: HB vs. F2F). Additional aims were to investigate if student perceptions of learning epistemology and learning factors were related to course format. Students (n = 110) in four introductory biomechanics courses (two F2F, two HB) completed the 24-question Biomechanics Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Because the results of this study have strategic implications for designing online learning that considers psychological factors and future researchers. This research also supports previous research (Knudson, 2010;Wallace & Knudson, 2020), one of the strongest variables related to learning is the psychological factor, namely learning motivation in these subjects. It is more Zapata-Cuervo, Montes-Guerra, Shin, Jeong, and Cho, (2021) found that students' self-effi cacy signifi cantly aff ects learning outcomes.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…Because the results of this study have strategic implications for designing online learning that considers psychological factors and future researchers. This research also supports previous research (Knudson, 2010;Wallace & Knudson, 2020), one of the strongest variables related to learning is the psychological factor, namely learning motivation in these subjects. It is more Zapata-Cuervo, Montes-Guerra, Shin, Jeong, and Cho, (2021) found that students' self-effi cacy signifi cantly aff ects learning outcomes.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…The challenge is to apply both anatomical/physiological bases and mechanical concepts (mathematics and physics) to observe/describe/measure human movement from a number of different applications that cut across the sub-areas of movement sciences (sport, ergonomics, injury, clinical rehabilitation, etc.) [61,62]. Additionally, new teaching innovative methodologies to evaluate human movement (Wii Balance Board platform, Kinect, smartphone applications, etc.)…”
Section: Practical Applications For Education and Researchmentioning
confidence: 99%
“…Essential for the professional development of specialists in physical education, a robust foundation in biomechanics enhances their practical applications. However, deficiencies in this foundational knowledge can lead to challenges in its practical application, indicating a potential need for enhancements in the pedagogical approaches used to teach biomechanical concepts in undergraduate courses [11,12,13]. Given its broad applications and impact on professional practice, the study of biomechanics is fundamental in preparing students for real-world challenges in physical activities and health-related fields.…”
Section: Introductionmentioning
confidence: 99%